Studi Kepustakaan Mengenai Pengaruh Teknik ABCDEF Dalam Konseling REBT - Alvin Faiz Adzikra; Hanifara Dyasti Rahayu; Najwa Anisa Fitri; Imalatul Khairat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to explore the ABCDEF technique in Rational Emotive Behavior Therapy (REBT) through a literature review approach. The ABCDEF model is an extension of the original ABC framework, incorporating additional stages: Disputation (D), new Effect (E), and Future Plan (F). These additional components strengthen the counseling process by emphasizing belief rationalization, emotional adjustment, and strategic planning for psychological challenges. The analysis is carried out descriptively by categorizing the information into key themes: structural framework, practical effectiveness, and case-based implementation. The findings indicate that the ABCDEF technique is effective in helping counselees identify irrational beliefs, form rational thought patterns, and develop adaptive future responses. This technique proves applicable in various contexts, including educational, clinical, and organizational settings. Moreover, the ABCDEF approach contributes significantly to the enhancement of individuals’ critical thinking and emotional regulation skills.